New species of the copepod genus Anthessius Della Valle, 1880 (Poecilostomatoida: Anthessiidae) from Turbo marmoratus Linnaeus (Gastropoda: Turbinidae) collected during the KUMEJIMA 2009 Expedition - Uyeno, Daisuke; Nagasawa, Kazuya (Zootaxa, 2012)
Anthessius isamusi n. sp. is described based on female and male specimens from a turbinid gastropod, Turbo marmoratusLinnaeus, collected in the East China Sea off Kumejima Island, the Ryukyu Islands, southern Japan, during the KUME-JIMA 2009 Expedition. The female of the new species is differentiated from its congeners by the following combinationof characters: 1) the absence of denticles on the ventral surface of the anal somite; 2) the length to width ratio of the caudalramus; 3) the antenna bearing 4 claws; 4) the maxilla with 3 distal teeth; 5) the exopod of leg 4 with 3 spines on the terminal segment, and; 6) leg 5 with a rod-like terminal segment.